The number of regulatory T cells in prostate cancer is associated with the androgen receptor and hypoxia-inducible factor (HIF)-2alpha but not HIF-1alpha. - Fox, S; Launchbury, R; Bates, G; Han, C; Shaida, N; Malone, P; Harris, A; Banham, A (2007)
BACKGROUND: Regulatory T cells (T(R)) mediate peripheral immunological tolerance and are implicated in tumor progression. Because prostate cancer is being investigated for treatment by immunotherapy, we have assessed tumor T(R) in prostate cancers. METHODS: T(R) cells were identified by FOXP3 in tissue microarrays (TMAs) from 146 radical prostatectomies and correlated with clinicopathological tumor parameters and prostatic specific antigen rise (PSA). RESULTS: Twenty of 146 tumors contained no T(R). The mean of the average for the remaining 146 patients was 7.24. There was a significant correlation between T(R) and androgen receptor (P=0.003) and with hypoxia-inducible factor (HIF)-2alpha (P=0.007) but not HIF-1alpha (P=0.25). There was no significant correlation between T(R) numbers and stage, capsular invasion, urethral margins, vascular invasion, Gleason score, pre-operative PSA, or time to PSA recurrence (all P>0.05). CONCLUSIONS: T(R) in prostate tumors shows significant heterogeneity and may be the result of hormonal and hypoxic signaling. Targeting these may reduce T(R) in tumors allowing more successful immune therapies.